Predictors of students’ adjustment during the transition to university in Spain - Páramo Fernández, María Fernanda (2017)
Background: Adjustment to university is a major life transition that not all emerging adults manage successfully. The Student University Adjustment Questionnaire is the instrument most commonly used to evaluate this multidimensional construct. Research in Spain on the predisposing factors for successful adjustment to university in emerging adults is scarce relative to the large number of studies carried out in North America. The objective of the present study was to analyze the association between students’ gender, family background, pre-university achievement and adjustment to university. Method: Participants were 300 Spanish fi rst-year students (198 women and 102 men) of mean age 18.02 years. Results: Pre-university achievement was the only signifi cant predictor of academic, social and institutional adjustment. Gender directly affected personal-emotional adjustment and indirectly affected academic adjustment mediated by entry grade. Conclusions: Students’ entry characteristics predict adjustment to university in the fi rst year. These fi ndings have important theoretical and practical implications.